Development of Science E-Module Based on Case Method to Im-prove Students’ Problem Solving Skills - Aribowo, Litasari Aldila; Kholil, Putri Alifa; Wulandari, Tiara Dwi (Universitas Negeri Semarang, 2025)
Life in the 21st century is full of challenges and problems that need to be solved in order to survive in global competition. This condition makes science education in the 21st century must be able to produce graduates who are not only good at knowledge, but also have critical thinking skills, creativity, collaboration, communication, not to mention problem solving. The purpose of this study was to analyze the effectiveness of e-modules based on case methods to improve the problem solving skills of prospective science teachers. This research uses RnD with the ADDIE model. Then e-module based on case methods that has been developed is implemented in basic science learning with a quasi-experimental design Nonequivalent control group design. Data analysis was conducted with the validity, characteristics, and effectiveness of e-modules based on case methods. The results showed that the e-module based on case methods was valid for use with a value of 0.98. The implementation of e-modules showed an increase in pretest and posttest results with an experimental class n-gain score of 0.85 with high criteria, while the control class n-gain score was 0.68 with moderate criteria. The conclusion of this study is that the e-module based on case methods is effectively used to improve the problem solving skills of prospective teacher students in Basic Science courses.